Enhancement Of eMuseum: Prototype Development Of Exhibit, Informative And E-Commerce Application - Norhayati, Izhar (2008)
The Government of Malaysia has encourage the use of information Technology application among the public and private sector to enable both sector to compete and provide better facilities to the nation. In the education sector, the Ministry of Education had provided a module to teach children about computer at the age of six in primary school. Most brick and mortar or physically located organizations also have seeked alternatives to do business particularly via online. Malaysians have adopted to online transactions with most of the government agencies via the Internet. The Ministry of Unity, Culture, Arts and Heritage had developed a website which is accessible to anyone and anywhere in the world who seeks information about Malaysian culture and heritage. Bringing museum online is a new perspective in exhibiting the cultural and heritage. Public authorities or private entities are the bodies that have undertaken efforts to digitalize this important heritage.